2023
DOI: 10.1111/ggi.14620
|View full text |Cite
|
Sign up to set email alerts
|

Association between the anthropometric measurements and dietary habits on telomere shortening in healthy older adults: A‐cross‐sectional study

Abstract: This study aimed to evaluate the effect of anthropometric measurements and dietary habits on telomere length in healthy older residents in rural and urban areas.Methods: This was a cross-sectional study. The study population included 81 healthy older individuals aged ≥80 years. A quantitative food frequency questionnaire was used to determine dietary habits. Anthropometric measurements were taken by researchers. The telomere length of individuals was determined from leukocytes using quantitative polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…In general, it has been accepted that the process of telomere shortening can be lowered through the adoption of lifestyle choices that are linked to decreased levels of oxidative stress [126,135,138,139]. Focusing on diet, several studies have revealed an association between a healthy food pattern and longer telomeres [65,71,140]. The MedDiet has been reported to stimulate telomerase activity in peripheral blood mononuclear cells, and if combined with moderate exercise, this diet can improve endothelial microvascular and cardiorespiratory functions, which is important for both better health and increased life expectancy [141].…”
Section: Discussionmentioning
confidence: 99%
“…In general, it has been accepted that the process of telomere shortening can be lowered through the adoption of lifestyle choices that are linked to decreased levels of oxidative stress [126,135,138,139]. Focusing on diet, several studies have revealed an association between a healthy food pattern and longer telomeres [65,71,140]. The MedDiet has been reported to stimulate telomerase activity in peripheral blood mononuclear cells, and if combined with moderate exercise, this diet can improve endothelial microvascular and cardiorespiratory functions, which is important for both better health and increased life expectancy [141].…”
Section: Discussionmentioning
confidence: 99%